Effectiveness of base isolation for asymmetric plan RC building using deterministic and stochastic approach - Aniket, Phadtare; Patil, V.S. (Journal of Structural Engineering, 2024)
The present study focused on seismic performance estimation of a base-isolated plan asymmetric reinforced concrete building by deterministic and by stochastic approach. Five-storey, plan asymmetric RC building for school with lead rubber bearing as the base isolation system and situated in India’s seismic zone was considered. Dynamic response inelastic and inelastic range has been assessed using a deterministic approach using response spectrum and pushover analysis. Storey shear, bending moment, displacement, ductility, damage pattern and oscillation modes were assessed by comparing the analysis results of a fixed base and base-isolated building. Effect of base isolation has also been studied by the probabilistic approach. Incremental dynamic analysis based fragility curves have developed using near field and far-field records. The peak ground acceleration was considered as an intensity measure, and Maximum Interstory Drift Ratio (MIDR) was considered as an engineering demand parameter. Three sets of ground motion were considered. First set is ground motions from far-field, the second set is ground motions from the near field with PGV: PGA ratio less than 150 (cm/s/g) and the third set is ground motions from the near field with PGV: PGA ratio greater than 150 (cm/s/g). The fragility curves were plotted for threshold damage states namely, slight, moderate, extensive and complete. The base-isolated building is modelled in SAP2000 v20 in which lead rubber bearing was modelled as nonlinear link element. The study concludes that base isolation has improved the seismic performance of an asymmetric plan building inelastic as well as in inelastic range with respect to various structural response parameters, failure mechanism etc. and hence is very useful.